Impact of IT on Knowledge Management: A Study of Yemeni Banks - Mhoub, Ahmed Abdullah Farhan; Al-Sanafi, Abdullah Abdullah Abdullah; Ghallab, Abdullatif Saleh Naser (University of Science and Technology, 2021)
This study aimed to assess the impact of IT dimensions (devices and equipment; software; data bases; networks; human element) on knowledge dimensions (generating knowledge; storing knowledge; sharing knowledge; applying knowledge). It also aimed to identify the level of differences among the study sample regarding the level of applying knowledge management in Yemeni banks attributed to demographic variables (gender; age; education; position; years of experience; ways of acquiring knowledge). To achieve this, the descriptive analytical method was used, and a questionnaire was administered to collect data. The population was all general departments in the Yemeni banks, of which (290) members were selected by the simple random method. (252) questionnaires were valid for analysis which were analyzed by the SPSS, using descriptive and inferential statistics. Major findings revealed that IT is crucial for knowledge management in banks. The IT dimension that had the highest impact on knowledge management was the human element, whereas the lowest was devices and equipment. On the other hand, knowledge management had no differences attributed to gender, age, position and ways of acquiring knowledge, but there were differences attributed to education variable. Yemeni banks were recommended to keep abreast of IT developments, and to facilitate the application of knowledge management in order to develop knowledge and improve services.